Stronger Headwinds Bring New Challenges for the Government - Morisset, Jacques (World Bank, Washington, DC, 2020)
With rising global health and economic concerns, Vietnam economy is expected to be significantly affected, even though the COVID 19 health crisis has been so far contained, with only 240 cases of infected people and no registered death as of early April. The World Bank’s GDP growth forecast for Vietnam has been cut by half compared to pre-crisis projections, with new forecast at 3.0 percent in 2020. Both the fiscal and external accounts are expected to deteriorate, creating a fiscal financing gap of approximately 5 billion dollars that will require new borrowings. The Government’s fiscal response, a combination of tax and social protection measures, is expected to attenuate the short-term economic costs associated to the COVID 19 pandemic, but the key challenges will be the rapid and effective implementation of the above measures and preparing the economy for the expected rebound when the health crisis is contained. Easing monetary and credit policies creates a welcome buffer to the affected businesses, but close monitoring is required as banks become increasingly exposed to the economic slowdown, affecting their asset quality, liability, and profitability over time. Potential areas for collaboration between the Government and the World Bank could include (i) macro and fiscal monitoring; (ii) implementation of social protection measures; and (iii) reforms to be implemented for optimizing the rebound of the economy.